The fakir miskin category of asnaf in Brunei Darussalam: the study on had kifayah (zakat poverty line) and the factors influencing the application of zakat / Nurol Huda Pehin Ismail, Mas Nooraini Mohiddin and Nurzakiah Ramlee - Ismail (Datu Seri Maharaja Dato Seri Utama (Dr) Haji), Nurol Huda Pehin; Mohiddin, Mas Nooraini; Ramlee, Nurzakiah (Universiti Teknologi MARA, 2021)
Fakir miskin (the poor) is the first category of asnaf mentioned in verse 60 of Surah al-Taubah (9:60) who are entitled for zakat. This prioritisation indicates the distinct character of their hardship from other categories of asnaf and the need for their welfare to be attended to. The question is how can they be recognised to determine their eligibility to the distribution of zakat. Hence, the objectives of this study are to elucidate the categorisation of fakir miskin based on their standard of living and to establish had kifayah (zakat poverty line) as the mechanism to determine the standard basic needs of a person and his dependants. Furthermore, this study aims to identify the factors that cause/persuade them to apply for zakat. Qualitative research method is employed for the purpose of this study, which is library-based. Data extracted and collected from literatures; books, articles, working papers, and the internet are analysed. Finding of this study shows that had kifayah is different from one person to another. The main reasons for the application for zakat by fakir miskin are found to be as financial aid to cover basic needs and as capital to start a business or venture into agriculture and the like.